Synthesis and characterization of new phthalocyanines providing effective singlet oxygen production and comparison of photochemically and sonophotochemically methods - Aksoy, Fulya; Kilicarslan, Fatma Aytan; Karanlik, Ceren Can; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The recently significant results in effective medical treatment in Sonophotodynamic Therapy (SPDT) applications have highlighted the importance of the design of new sonosensitizers/sonophotosensitizers. Thanks to their versalite molecular structure and tunable photophsicochemical features, phthalocyanines have gained remarkalbe attention. Encouraged by these results bis 4-[(6-bromonaphthalene-2)-ol] substituted metallophthalocyanines at peripheral positions were synthesized and characterized. The singlet oxygen production capacities of the newly synthesized compounds were investigated in sonochemically, photochemically and sonophotochemically. In all experiments, InPc-4 have highest singlet oxygen production capacity. Zn-Pc and MgPc singlet oxygen quantum yield were 0.38 and 0.28 in photochemical methods. Obtained result showed that, InPc is a promising sensitizer for all application. On the other hand MgPc and ZnPc are suitable for sonophotochemically applications.
Keywords: Phthalocyanine; Photodynamic therapy; Combination therapy; Singlet oxygen generation; AGGREGATION; THERAPY; Chemistry; Crystallography